Expansion and Contraction of Scripture: The Ritual (Im)purity of Unbelievers According to Shīʿa Jurisprudence - Pargoo, Mahmoud (Islam and Christian-Muslim relations, 2018)
An indispensable step in extrapolating a specific Sharia ruling is to find parts of the Scripture that have addressed the question at hand. This article addresses the process of scriptural prooftext finding and, based on the investigation of the Twelver Imāmī jurists' views about the (im)purity of unbelievers, argues that, though textual sources of the Sharia as a whole (the Qur'an and the Hadith compendia) are fixed, textual sources for a single case ruling may vary widely from one jurist to another. There is no fixed rule to restrict jurists to a specific set of verses of the Qur'an or passages of the Hadiths for a legal problem; any of the tens of thousands of these verses and Hadiths could - if deemed relevant by a jurist - become a scriptural reference for a specific ruling. A verse of the Qur'an that has never been used as a prooftext for a certain ruling could later be used as an authentic source either for or against that ruling. In other words, the Scripture as a source for specific legal rulings is capable of expanding and contracting.